Preliminary Research on the Development of E-Module Learning Media with Ethno-STEAM Approach to Increase Scientific Literacy - Amanah, Makripatun; Sudarmin, Sudarmin; Haryani, Sri (Unnes Science Education Journal, 2023)
This research is a preliminary study regarding the description of teacher-led learning, students scientific literacy abilities, and the need for developing Ethno-STEAM integrated e-media on pollution material to increase students literacy. This research used the descriptive method. The subjects of this research were 64 students in class X and 4 science teachers at SMK Takhassus Al Qur’an Wonosobo. The data collection instruments used were questionnaires, interview guides, and scientific literacy test questions. Based on the results of interviews with teachers, it shows that students’ scientific literacy abilities are still lacking. It can be seen from the results of the students’ scientific literacy test, which showed a percentage of 39%. On the indicator identifying keywords to gain scientific information, most of the students answered correctly with a percentage of 71%, while on the indicator recognizing scientific inquiry features, only 42% of students could answer correctly due to a lack of scientific literacy and student knowledge about technology use. Based on the results of the questionnaire analysis, Ethno-STEAM integrated e-media to increase students’ scientific literacy as an alternative learning medium on pollution material is needed to be developed with a percentage of 84%. The use of Ethno-STEAM integrated e-media is expected to increase students’ understanding, provide meaningful learning for students through the application of ethnoscience, and improve students’ scientific literacy skills.